Youth Readiness for Family Life Through the BKR Program in Gelang Village: Persiapan Pemuda untuk Kehidupan Keluarga Melalui Program BKR di Desa Gelang - Ulyah, Roudhotul Syarifah; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Early marriage and juvenile delinquency remain social problems affecting youth and family quality in Indonesia. Specific Background: The Bina Keluarga Remaja (BKR) program aims to educate adolescents on reproductive health, life skills, and family preparedness. Knowledge Gap: Implementation challenges of BKR at the village level remain underexplored, particularly in Sidoarjo Regency. Aims: This study analyzes the implementation of the BKR Program in Gelang Village and evaluates its outcomes using Edy Sutrisno’s effectiveness indicators. Results: The findings show partial program success: adolescents’ understanding of reproductive health improved, and early marriage rates declined, but participation and consistency remain low due to limited human resources and irregular activities. Novelty: The research applies a five-indicator model of effectiveness to assess qualitative outcomes of youth development programs. Implications: Strengthening stakeholder collaboration, increasing youth participation, and ensuring regular monitoring are necessary for sustainable BKR implementation. Highlights: BKR improves youth awareness and family readiness. Limited resources hinder program consistency. Continuous collaboration sustains program outcomes.